Design of low voltage micropower asynchronous datapath modules for a multiplierless FIR filter - Chua, Chien Chung. (2008)
The analysis, design and implementation of datapath modules for a “multiplierless” asynchronous Finite-Impulse-Response (FIR) digital filter. We adopt both the multiplierless and asynchronous approaches as they potentially offer a power dissipation advantage.